What Others Need: Misperceptions of Well-Being Norms and Support for Redistribution - Anthony Lepinteur; Nattavudh Powdthavee (Institute of Labor Economics (IZA), 2025)
People often misjudge what others need to live well. We introduce and measure well-being norms - the income people believe others require for a good life - and show that these beliefs are systematically underestimated. In a preregistered U.S. survey, 85–86% of respondents reported thresholds below what others say they themselves need. Two randomized survey experiments corrected these misperceptions. Respondents updated their beliefs considerably, yet support for redistribution and donation behavior remained unchanged. This null average effect, however, masks substantial heterogeneity. Among those who found the information credible and personally relevant, we observe redistribution support increasing by approximately 20% of a standard deviation, especially when the information referred to low-income families rather than the average American. Among those who dismissed it, we observe support decreasing by similar magnitudes - a pattern consistent with motivated reasoning and backlash. The main insight is that belief updating alone does not, on average, change policy preferences. Information influences redistribution attitudes only when perceived as morally important and legitimate.
Keywords: D31; D63; H23; H24; I31; 330; redistribution preferences; inequality; beliefs; information treatments; income; subjective well-being